Dinamika dan Daya Saing Sektor Pertanian di Kabupaten Padang Pariaman, Sumatera Barat - Zori Mahendra; Widya Fitriana; Yuerlita Yuerlita (Institut Pertanian Bogor, 2024)
Regional economic development is closely related to the role of the agricultural sector. In addition to food production, agriculture also contributes to the absorption of labor. During the COVID-19 pandemic, regional economic growth in Indonesia tended to decline, as well as in Padang Pariaman. Padang Pariaman will have a negative growth rate of 10.46% in 2020, the lowest compared to the average GDP growth rate of the other region in West Sumatra. This study aims to determine the dynamics and competitiveness of the agricultural sector compared to the other sectors. The research was conducted in a quantitative and descriptive manner using time series data for the period 2016–2020 from BPS. Data analysis using Klassen typology and shift share analysis. The results showed that the agricultural sector has an average share of 21.37% of the GDP of Padang Pariaman. Based on Klassen's typology analysis, the agriculture sector was included in the potential sector category in 2017–2019 but shifted to the developed sector category in 2020. Despite experiencing slow growth, the results of shift share analysis show that the agricultural sector in Padang Pariaman is still competitive. Increasing the competitiveness of the agricultural sector can be pursued by expanding sector linkages with the other economic sectors and increasing diversification of economics activities in agricultural sector Keywords: agricultural sector; shift share analysis; tipology klassen